Resolution and super‐resolution. Issue 6 (9th February 2017) - Sheppard, Colin J. R.
Abstract: Many papers have claimed the attainment of super‐resolution, i.e. resolution beyond that achieved classically, by measurement of the profile of a feature in the image. We argue that measurement of the contrast of the image of a dark bar on a bright background does not give a measure of resolution, but of detection sensitivity. The width of a bar that gives an intensity at the center of the bar of 0.735 that in the bright region (the same ratio as in the Rayleigh resolution criterion) is λ / ( 13.9 × numerical aperture ) for the coherent case with central illumination. This figure, which compares with λ / ( numerical aperture ) for the Abbe resolution limit with central illumination, holds for the classical case, and so is no indication of super‐resolution. Theoretical images for two points, two lines, arrays of lines, arrays of bars, and grating objects are compared. These results can be used a reference for experimental results, to determine if super‐resolution has indeed been attained. The history of the development of the theory of microscope resolution is outlined. Abstract : This shows the image of a dark bar on a coherent bright background, for different bar widths. There is no sharp cutoff. There is always a dip in intensity at the center, even for a bar width of, corresponding to 0.05 Airy units.